2020
DOI: 10.2478/amtsb-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Calcium Hydroxide as an Intracanal Medicament in the Treatment of Large Periapical Lesions. A Review

Abstract: Calcium hydroxide is a slow-acting antiseptic substance used in several forms for the last century in various fields of dentistry. Its applications in endodontics are by far the most meaningful including the treatment of root resorptions and perforations, inducing the apexification process, and most importantly as intracanal medicaments representing a crucial step in the nonsurgical management of large periapical lesions. The aim of this article is to conduct a review of the properties, antimicrobial effect, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In numerous studies, calcium hydroxide (CH) has been widely used as an intracanal medicament to combat regional microbiota. 6 , 7 However, it has been recently shown that CH is not as effective as speculated against intracanal microorganisms and cannot be addressed as a strong antibacterial agent despite having an alkaline pH. 8 Therefore, different studies have investigated new drugs or combination of drugs with more efficient antimicrobial activity as appropriate replacements for CH, for example, antibiotics, to be employed in endodontic treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In numerous studies, calcium hydroxide (CH) has been widely used as an intracanal medicament to combat regional microbiota. 6 , 7 However, it has been recently shown that CH is not as effective as speculated against intracanal microorganisms and cannot be addressed as a strong antibacterial agent despite having an alkaline pH. 8 Therefore, different studies have investigated new drugs or combination of drugs with more efficient antimicrobial activity as appropriate replacements for CH, for example, antibiotics, to be employed in endodontic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the application of intracanal medication has been deliberated over the years, using various types of drugs, including antibiotics. In numerous studies, calcium hydroxide (CH) has been widely used as an intracanal medicament to combat regional microbiota 6,7 . However, it has been recently shown that CH is not as effective as speculated against intracanal microorganisms and cannot be addressed as a strong antibacterial agent despite having an alkaline pH 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also suggest that this medicament inactive endotoxin thereby delaying the release of cytokines inflammatory mediators hence reducing the periapical inflammation. 2,3 It has been documented in several studies that the presence of calcium hydroxide on root canal, dentin wall can alter the effect of root canal treatment. It has been further explain that the residual of calcium hydroxide interact with Zinc oxide eugenol sealers to produce eugenolate.…”
Section: Introductionmentioning
confidence: 99%